Language Foregrounding and Structure of Literary Functions in Hossein Monzavi's Sonnet Using Leach's Linguistic Model - Abdollahi, Narges (2020)
Deviation and structural critique, as features distinguishing literary language from normative language, are the most fundamental concepts in structuralism theory. In this century, structuralism is a scientific and common approach to evaluate the artistic characteristics of literary works. Geoffrey Leach, an English structuralist, classified literary features (deviations) in eight levels: (1) lexical, (2) grammatical, (3) phonological, (4) graph logical, (5) dialectical, (6) stylistic, (7) semantic, and (8) historical period. He distinguished these linguistic deviations from other deviations by using three features of position, direction, and conclusiveness. His model is generalizable to all languages, especially Persian. Forasmuch, as Monzavi's sonnet, has a specific position in the contemporary Persian poetry. This study aimed to find language deviations in Monzavi's sonnets using descriptive-analytical method within the framework of the structuralism and based on Leach’s deviation Model. Accordingly, the poet’s deviations and artistic creations are often sought for simplicity in the language of poetry and its approach to common language (simple and impossible). In general, the most frequent type of deviation in Monzavi's sonnet in both qualitative and quantitative terms is semantic deviation.